The Analisis Determinan Efek Samping Pasca Vaksinasi Covid-19 pada Lansia di Wilayah Kerja Puskesmas Multiwahana - Yusni Kurniasari; Dian Eka Anggreny; Dianita Ekawati (STIKes Payung Negeri Pekanbaru, 2022)
The world wide is currently facing a health crisis that takes over the human living. The spread of Corona Virus Disease 2019 (COVID-19) all over the world is increasing time after time causing the loss of both lives and materials. It is also has been impacted through the social aspects, economics, and public welfare. COVID-19 is an infectious disease caused by the new variants of Coronavirus. This research used a cross-sectional study design. The population of this study is all people aged 60 years in the working area of ​​the Multiwahana Health Center who have received doses of COVID-19 vaccinations 1 and 2. The research sample was 96 respondents, sampled using a simple random sampling technique. Statistical test using chi-square and multiple logistic regression with a significance level (α=0.05). The result shows that there is the correlation between gender (p = 0.020), blood pressure (p = 0.016), history of allergies (p=0,001), comorbidities (p=0.007) and family support (p=0.008). The most dominant multivariate variable that relates to the post-COVID-19 vaccinations side effect is the history of allergies on a p-value equal to 0,001< α (0,05). The conclusion from the research is there was a correlation between gender, blood pressure, history of allergies, comorbidities, and family support with side effects after the COVID-19 vaccination.